Caregiver report versus clinician impression: disagreements in rating neuropsychiatric symptoms in Alzheimer's disease patients. (9th March 2015) - Stella, Florindo; Forlenza, Orestes Vicente; Laks, Jerson; de Andrade, Larissa Pires; de Castilho Cação, João; Govone, José Sílvio; de Medeiros, Kate; Lyketsos, Constantine G.
Abstract: Background: The measurement of neuropsychiatric symptoms (NPS) in dementia is often based on caregiver report. Challenges associated with providing care may bias the caregiver's recognition and reporting of symptoms. Given potential problems associated with caregiver report, clinicians may improve measurement by drawing from a wider array of available data and by applying clinical judgment. Objective: The objective of this study is to evaluate potential disagreements between caregiver report and clinician impression when rating psychopathological manifestations from the same patient with dementia. Methods: Three hundred twelve participants (156 patients with Alzheimer's disease [AD] and 156 caregivers) were studied using the Neuropsychiatric Inventory–Clinician Rating Scale. We considered disagreement to be present when caregiver ratings were significantly higher or lower ( p  < 0.05) than NPS ratings by clinicians of the same patient. To evaluate whether disagreements were related to dementia severity, we repeated comparisons across levels defined by the clinical dementia rating. Results: The most common disagreements involved ratings of agitation, depression, anxiety, apathy, irritability, and aberrant motor behavior especially in patients with mild dementia. There were fewer discrepancies in moderate or severe dementia. The most consistent disagreements involved global ratings of depression where caregiver scores ranged from +22.5 higher to −4.5 lower than clinician rating. Conclusions: Caregivers may have incomplete perception of patient NPS mainly in mild dementia. NPS ratings might be confounded by cultural beliefs, sometimes leading caregiver to interpret symptoms as part of "normal" aging. Copyright © 2015 John Wiley & Sons, Ltd.